ANALISIS ZAKAT HASIL PETANI WALET TERHADAP KESEJAHTERAAN MASYARAKAT DI DESA PANCAWARNA KEC. PEDAMARAN TIMUR KAB. OGAN KOMERING ILIR - Thariska Oktaviani; Zuul Fitriani Umari; Iceu Sri Gustiana (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze the management of zakat from swiftlet farming and its impact on the welfare of the community in Pancawarna Village, Pedamaran Timur Subdistrict, Ogan Komering Ilir Regency. The research employed a descriptive qualitative method, collecting data through observation, interviews, and documentation. Informants included swiftlet farmers, village officials, and zakat recipients. The results indicate that most swiftlet farmers have not fully understood their obligation to pay zakat from their business, and there is no official village-level zakat management institution. Some commun ity members distribute their income in the form of donations, such as money or basic necessities, but this has not yet complied with Islamic law. The low implementation of zakat is influenced by limited religious knowledge, economic instability due to fluctuations in swiftlet nest prices, and insufficient outreach from the government and zakat institu tions. The study concludes that while the potential of swiftlet business zakat is significant, it has not yet substantially improved community welfare. Therefore, guidance, education, and more effective zakat management are necessary to maximize its role as an economic instrument for social welfare.